Left hemisphere lateralization in unilateral upper motor neuron dysarthria via quantitative acoustic analysis - Yiqi Cao; Yazhuo Cheng; Shuhao Liu; Zhiwei Mou (Scientific Reports)
Abstract This paper aimed to identify specific acoustic parameters F1, F2, and Vowel Space Area (VSA), Vowel Articulation Index (VAI), Formant Centralization Ratio (FCR) for evaluating speech in Mandarin-speaking individuals with Unilateral Upper Motor Neuron (UUMN) dysarthria. Additionally, it explored the correlation between dysarthria severity and lesion side based on these parameters and scale results. This study conducted comparative study using acoustic spectral analysis to analyze phonetic features among UUMN dysarthria (UUMND) patients and neurologically normal adults, and the Left-sided and Right-sided upper motor neuron dysarthria (UMND) groups. The Mandibular-Oral Motor Function Assessment Scale (MOMFAS) was used in the study. The acoustic parameters F1, F2 and VSA, VAI, FCR showed significant differences between individuals with UUMN dysarthria and neurologically normal adults. Comparing left-sided upper motor neuron (UMN) dysarthria patients with right-sided UMN dysarthria patients, a considerable increase in FCR was observed in the left-sided group, while VSA and VAI showed significant decreases. The mean scale score of left-sided UMN dysarthria patients was also significantly lower than that of individuals with right-sided UMN dysarthria. The severity of UUMND was more pronounced in individuals with left-sided lesions, providing supportive evidence of lateralization on the left hemisphere. The acoustic indices F1, F2 and VSA, VAI, FCR can sensitively reflect the vowel changes of UUMND patients. They could be utilized not only to describe the acoustic properties of UUMND patients but also to assess the effectiveness of rehabilitation therapy on impaired vowel articulation in such patients.